The Process of Social Innovation Program Charm Walahar Creative Destination “Revitalization of Lake Kalimati Becomes Ecotourism (Tourism Renaldi) and Environmentally Friendly Energy Technology for Mandiri UKMKM (Teh Umi)” PT Pertamina Patraniaga Fuel Terminal Cikampek - Ismail, Taufik; Algifari M, M Zakky; Insani M, Cita (Journal of World Science, 2022)
Introduction: Social and Environmental Responsibility Program is an act of the company from its commitment to contribute to sustainable development with an economic, environmental, and social impact. The purpose of this study was to analyze the Walahar Creative Destination program in the form of developing ecotourism and environmentally friendly alternative energy potential through Revitalizing Lake Kalimati into Ecotourism. Methods: The research method used in this study is a descriptive research method with a qualitative approach. Result: The social innovation of Revitalizing Lake Kalimati into Ecotourism has gone through the first stage of the process, namely potential analysis and rebranding by conducting an appropriate possible assessment and rebranding the name from Lake Kalimati to Lake Cinta. The second stage is the Forum group discussion (FGD) and agency coordination involving various parties, starting from the Regional Government, Village Government, Perum Jasa Tirta II, and different elements of society. The third stage is the management of permits legally following applicable regulations. The fourth stage is training and coaching to improve soft and hard skills. The last is the execution stage for constructing Lake Cinta facilities and infrastructure. Conclusion: The appropriate process stages make applying social innovations to the community easy to accept and use. The resulting benefits can be felt economically, socially, and environmentally.